Evaluation of Noise Exposure and Hearing Threshold Levels Among Call Centre Operators - PAWLACZYK-ŁUSZCZYŃSKA, Małgorzata; ZAMOJSKA-DANISZEWSKA, Małgorzata; ZABOROWSKI, Kamil; DUDAREWICZ, Adam (Archives of Acoustics, 2019)
The aim of this study was to evaluate the hearing status of call centre operators in relation to their noise exposure. Conventional pure-tone audiometry and extended high-frequency audiometry were performed in 49 workers, aged 22–47 years (mean ± SD: 32.0 ± 6.0 years), working in call centre from 1.0 to 16.5 years (mean ± SD: 4.7 ± 2.9 years).Questionnaire inquiry aimed at collecting personal data, the information on ommunication headset usage habits, self-assessment of hearing ability and identification of risk factors for noise-induced hearing loss were also carried out. Sound pressure levels generated by the communication headset were determined using the artificial ear technique specified in CSA Z107.56-13 (2013) standard. The background noise prevailing in offices was also measured according to PN-N-01307 (1994) and PN-EN ISO 9612 (2011).Personal daily noise exposure levels in call centre operators varied from 66 to 86 dB (10–90th percentile). About half of the study subjects had normal hearing in the standard frequencies (from 250 to 8000 Hz) in both ears, while only 27.1% in the extended high-frequencies (9–16 kHz). Moreover, both high-frequency and speech-frequency hearing losses were observed in less than 10% of audiograms, while the extended high-frequency threshold shift was noted in 37.1% of analysed ears. The hearing thresholdlevels of call centre operators in the frequency of 0.25–11.2 kHz were higher (worse) than the expected median values for equivalent (due to age and gender) highly screened population specified in ISO 7029 (2017). Furthermore, they were also higher than predicted for 500–4000 Hz according to ISO 1999 (2013) based on the results of noise exposure evaluation.